The relationship between feeding patterns and the nutritional status of preschool children - Mirna Fauziati; Elvi Maisara; Yusri; Laina Noviana; Desna Maulinda (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Feeding patterns are a critical factor influencing a child's growth, development, and nutritional status. Inappropriate feeding practices can contribute to nutritional problems such as wasting, stunting, overweight, and micronutrient deficiencies. UNICEF data (2022) shows that two in five children under five do not receive the recommended dietary diversity, and only around 40% receive an optimal diet. Purpose: to determine the relationship between feeding patterns and the nutritional status of pre-school children aged 3-5 years. Method: The study employed a quantitative design with an analytical study and a cross-sectional approach. The population was 4.041 toddlers in the Banda Sakti Community Health Center working area, with a sample of 107 respondents selected using accidental sampling. Data collection was conducted using primary and secondary data, then analyzed using the Chi-Square test. The study was conducted from July to August 2025. Results: The results of the analysis showed a p-value of 0.000 (<0.05), so there is a significant relationship between feeding patterns and the nutritional status of preschool children aged 3–5 years. Conclusion: Good feeding patterns are associated with optimal nutritional status in preschool children. Therefore, it is necessary to increase parental awareness, especially mothers, regarding the importance of implementing appropriate feeding patterns to prevent nutritional problems in children.